The Effect of Financial Literacy, Life Style, Financial Attitude and Locus of Control to Financial Management Behavior - Amila Syaliha; Entar Sutieman; Muhamad Ridwan Pasolo; Victor Pattiasina (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2022)
This study was conducted to examine whether Financial Literacy, Lifestyle, Financial Attitude and Locus of Control have an effecton Financial Management Behavior in Accounting Students at Yapis University, Papua. The population in this study were all active and registered accounting students at Yapis University Papua. Samples were taken using purposive sampling method with a sample size of 50 respondents. The data used in this study were obtained using a questionnaire. Data analysis was performed using multiple linear regression analysis. Based on the results of the study, it shows that financial literacy and locus of control have a positive and significant effect on financial management behavior in accounting students at Yapis University, Papua. While lifestyle and financial attitudes have no positive and insignificant effect on financial management behavior in accounting students at Yapis University Papua.